2008
DOI: 10.3171/jns/2008/109/11/0811
|View full text |Cite
|
Sign up to set email alerts
|

Transient expansion of vestibular schwannoma following stereotactic radiosurgery

Abstract: Transient expansion of VSs after GKS was found to be much more frequent than previously reported, strongly suggesting a correlation with deterioration of facial and trigeminal nerve functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
107
3
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(119 citation statements)
references
References 27 publications
5
107
3
2
Order By: Relevance
“…Overall, tumor response was comparable to published results [1,[9][10][11][12][13][14][15][16] with 94 % of tumors being controlled. However, there was a significant proportion of patients (39 %) who demonstrated transient increases in tumor volume on MRI, or "pseudoprogression" before eventual tumor regression.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Overall, tumor response was comparable to published results [1,[9][10][11][12][13][14][15][16] with 94 % of tumors being controlled. However, there was a significant proportion of patients (39 %) who demonstrated transient increases in tumor volume on MRI, or "pseudoprogression" before eventual tumor regression.…”
Section: Discussionsupporting
confidence: 84%
“…This phenomenon is well recognized to occur in patients with gliomas treated with fractionated radiation therapy [17]. More recently, several reports have emerged demonstrating transient tumor volume increases in VS treated with stereotactic radiosurgery [8,[13][14][15][16]. To our knowledge, there is only one other report in the literature by Shirato et al of transient tumor volume increases after fractionated radiation therapy for VS [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although an association between transient volume expansion and cranial nerve (5th or 7th) dysfunction was reported in several studies, the correlation between transient volume expansion and hearing deterioration remains controversial [9,11,21] . Nagano et al [21] and van Eck and Horstmann [6] reported that transient volume expansion was observed in more than half of their patients within 1 year; however, this did not correlate significantly with hearing deterioration. In contrast, Wowra et al [9] reported that risk of hearing loss was significantly correlated with transient tumor swelling.…”
Section: Prognostic Factors Of Hearing Preservationmentioning
confidence: 99%
“…that we should accept the 6 25% increase as a significant value of transient volume expansion since a volume change of 6 10% may result from error of calculation [9,11,21] . Although an association between transient volume expansion and cranial nerve (5th or 7th) dysfunction was reported in several studies, the correlation between transient volume expansion and hearing deterioration remains controversial [9,11,21] .…”
Section: Prognostic Factors Of Hearing Preservationmentioning
confidence: 99%